"Aren't Labels for Pickle Jars, Not People?" Negotiating Identity and Community in Talk About 'Being Gay'. (November 2014) - Adams, Jeffery; Braun, Virginia; McCreanor, Tim
Understanding how people in any given population think about and experience their sexuality is fundamental to developing and implementing good health policy, research, and practice. Yet despite several decades of focus on sexual identity and HIV risk within health research, gay men as a category are often treated in an uncomplicated way. This article reports on focus group discussions held with 45 gay and other men who have sex with men in New Zealand to identify how they talked about issues of gay identity and gay community/ies. The men negotiated and renegotiated their gay identity and being gay was reported as just one part of most men's lives. Many men did not like to be labeled as gay and downplayed aspects of their gay identity. Only a few men proclaimed being gay. Men reported very mixed experiences with the gay community/ies. Understanding how men experience being gay, provides information vital to enhancing policy, research and practice responses to gay men's health issues. A major challenge for health service provision to appropriately engage with men who have sex with other men but resist being labeled as gay was identified.